Circ0007042 alleviates intervertebral disc degeneration by adsorbing miR-369 to upregulate BMP2 and activate the PI3K/AKt pathway - Zhenyu Wang; Yuguang Zhao; Yi Liu; Zhigang Qu; Xinming Zhuang; Qingxu Song; Haoyu Li; Jiali Leng (Arthritis Research & Therapy, 2022)
Abstract Background To identify regulatory ncRNA molecules that can cause differential expression of CDH2 in intervertebral disc degeneration (IDD) and explore whether there are other ways to affect the progression of IDD. Methods A primary culture of human nucleus pulposus (NP) cells was established and identified by immunofluorescence. An in vitro IDD model was constructed by compressing human NP cells, and the MTT assay was used to measure cell viability. Changes in the ncRNA group were analysed by RNA-seq. The expression levels of hsa_circ_7042, CDH2, and miR-369-3p were detected by qPCR. Cell apoptosis, senescence, and extracellular matrix (ECM) metabolism were detected by flow cytometry, β-galactosidase staining, and Western blotting. hsa_circ_7042, miR-369-3p, and bone morphogenetic protein 2 (BMP2) were verified by luciferase and RNA immunoprecipitation (RIP) analyses. The PI3K/Akt pathway was validated by transfection of BMP2 siRNA. Furthermore, a mouse model of lumbar spine instability was constructed. circ_7042 adenovirus was packaged and injected into the intervertebral discs of mice, and the influence of circ_7042 overexpression on intervertebral disc degeneration was determined. Results Western blotting, qPCR, and flow cytometry analyses confirmed that overexpression of circ_7042 could downregulate miR-369-3p and upregulate the expression of CDH2 and BMP2 in IDD cell and animal models. Additionally, the levels of apoptotic and senescent cells decreased, and ECM degradation decreased. The PI3K/Akt pathway was significantly activated after circ_7042 was overexpressed. The injection of circ_7042-overexpressing adenovirus effectively reduced ECM degradation and the level of apoptosis in NP tissue. Conclusions circ_7042 could upregulate the expression of CDH2 and BMP2 by absorbing miR-369-3p, and the increased BMP2 activated the PI3K/Akt pathway, thus improving IDD.